Coexistence, resource partitioning, and fisheries management: A tale of two mesopredators in equatorial waters - Danielle L. Orrell; Daniel Sadd; Kirsty L. Jones; Kate Chadwick; Tiffany Simpson; Darcy E. Philpott; Nigel E. Hussey (Journal of Fish Biology, 2025)
Rock hind ( Epinephelus adscensionis ) and spotted moray ( Gymnothorax moringa ) are ubiquitous mesopredators that co‐occur in the nearshore waters of Ascension Island in the South Atlantic Ocean, where they have significant cultural and subsistence value, but management of their non‐commercial take is limited. This isolated volcanic system is home to high biomass and low species diversity, which poses two key questions: How can two mesopredators that perform similar ecological roles coexist? And if these two species are so ecologically similar, can they be managed using the same approach? Here, we combined acoustic telemetry, stomach content analysis, and stable isotope analysis to (i) explore space use and diet choices within and between these two species and (ii) to assess appropriate species‐specific management options. Although rock hind had high residency and small calculated home ranges (0.0001–0.3114 km 2 ), spotted moray exhibited shorter periods of residency (

Carpooling with ecologists, geographers and taxonomists: perceptions from conducting environmental research in tropical regions - Kate Baker; Claas Damken; Jean-Luc Gattolliat; Ulmar Grafe; Rafhiah Kahar; Albert Orr; Michel Sartori; Rodzay A. Wahab; Herbert Zettel; Michael A. Chadwick (Biodiversity and Conservation, 2019)

Benthic community structure and ecosystem functions in above- and below-waterfall pools in Borneo - Kate Baker; Michael A. Chadwick; Rodzay A. Wahab; Rafhiah Kahar (Hydrobiologia, 2017)

Optic radiation structure and anatomy in the normally developing brain determined using diffusion MRI and tractography - Michael Dayan; Monica Munoz; Sebastian Jentschke; Martin J. Chadwick; Janine M. Cooper; Kate Riney; Faraneh Vargha-Khadem; Chris A. Clark (Brain Structure and Function, 2015)

Establishing Representative No‐Take Areas in the Great Barrier Reef: Large‐Scale Implementation of Theory on Marine Protected Areas - LEANNE FERNANDES; JON DAY; ADAM LEWIS; SUZANNE SLEGERS; BRIGID KERRIGAN; DAN BREEN; DARREN CAMERON; BELINDA JAGO; JAMES HALL; DAVE LOWE; JAMES INNES; JOHN TANZER; et al. (Conservation Biology, 2005)
The Great Barrier Reef Marine Park, an area almost the size of Japan, has a new network of no‐take areas that significantly improves the protection of biodiversity. The new marine park zoning implements, in a quantitative manner, many of the theoretical design principles discussed in the literature. For example, the new network of no‐take areas has at least 20% protection per “bioregion,” minimum levels of protection for all known habitats and special or unique features, and minimum sizes for no‐take areas of at least 10 or 20 km across at the smallest diameter. Overall, more than 33% of the Great Barrier Reef Marine Park is now in no‐take areas (previously 4.5%). The steps taken leading to this outcome were to clarify to the interested public why the existing level of protection was inadequate; detail the conservation objectives of establishing new no‐take areas; work with relevant and independent experts to define, and contribute to, the best scientific process to deliver on the objectives; describe the biodiversity (e.g., map bioregions); define operational principles needed to achieve the objectives; invite community input on all of the above; gather and layer the data gathered in round‐table discussions; report the degree of achievement of principles for various options of no‐take areas; and determine how to address negative impacts. Some of the key success factors in this case have global relevance and include focusing initial communication on the problem to be addressed; applying the precautionary principle; using independent experts; facilitating input to decision making; conducting extensive and participatory consultation; having an existing marine park that encompassed much of the ecosystem; having legislative power under federal law; developing high‐level support; ensuring agency priority and ownership; and being able to address the issue of displaced fishers.